Race differences in public satisfaction with and trust in the local police in the context of george floyd protests: an analysis of residents’ experiences and attitudes - Pryce, Daniel K. (Criminal justice studies, 2022)
Measuring public opinions about the police is a mainstay of police–community relations because the police need to know how well they are doing in the communities they serve. To understand public attitudes toward the police in the aftermath of George’s Floyd’s killing, we analyze data from residents across seven cities located in Southeast Virginia. We find that, compared to whites and other racial groups, blacks were more likely to report both personal and vicarious experiences and were less trusting of and satisfied with police. In addition, blacks were less likely than whites and other racial groups to support the police’s handling of peaceful protests in the wake of George Floyd’s death. Other demographic differences are found and presented in light of prior research on public attitudes toward the police. The implications of our findings for improved police–community interactions, policy, and future research are discussed.